A very rare cause of recurrent apnea: congenital nasopharyngeal teratoma - Ulger, Zülal; Egemen, Ayten; Karapinar, Bülent; Veral, Ali; Apaydin, Fazil (The Turkish Journal of Pediatrics, 2005)
A three-month-old girl patient born at the 37th week of gestation as one of twins was admitted to our hospital with cardiac arrest. There was past medical history of multiple hospitalizations with symptoms of cyanosis, respiratory distress, and frequent and severe attacks of apnea since her birth. On nasopharyngeal computerized tomography a mass (25x24 mm) occupying the right side of the nasopharynx was detected. The pathological evaluation of the excised mass revealed benign teratoma. After the removal of the nasopharyngeal mass under general anesthesia, respiratory distress and attacks of apnea disappeared completely. In every neonate with unexplained stridor and recurrent apnea, beside the common causes like respiratory distress syndrome, sepsis, and asphyxia, the possibility of oropharyngeal and nasopharyngeal mass should be kept in mind.